Ship Management Joint Venture (SMJV), PT Pertamina International Shipping (PIS) with Nippon Yusen Kabushiki Kaisha (NYK) - Indra Pasau, Yusuf; Dessy Winiastuty, Nuraini; Simarmata, Juliater (Green Publisher, 2025)
The Ship Management Joint Venture (SMJV) between PT Pertamina International Shipping (PIS) and Nippon Yusen Kabushiki Kaisha (NYK) aims to enhance the efficiency and effectiveness of ship operations. This study seeks to explore the collaboration strategies of both companies in facing intense competition within the ship management industry, as well as sustainability challenges related to carbon emission reduction. The objective of this research is to analyze the impact of SMJV on PIS's operational and financial performance, as well as to evaluate the synergies created through this partnership. The methodology employed includes in-depth interviews with managers from PIS and NYK, along with the analysis of documents related to post-implementation performance of SMJV. The findings indicate that this collaboration successfully reduced operational costs and improved customer satisfaction, with a revenue growth of 15% over the next two years. Furthermore, organizational culture challenges were addressed through cross-cultural training programs, improving communication and operational efficiency. Recommendations for PIS and NYK include continuously evaluating and developing the SMJV strategy, as well as strengthening risk management related to market changes. This study provides important insights into how SMJV can serve as a strategic model for other companies in the increasingly competitive and sustainable shipping industry.